MiR-7 mediates the signaling pathway of NE affecting FSH and LH synthesis in pig pituitary. Issue 3 (March 2020) - Li, Xin; Li, Hongjiao; Zhang, Di; Xu, Guojin; Zhang, Jinglin; Cui, Sheng
Abstract : MicroRNA-7 (miR-7) is an important modulator of a plenty of gene expressions and the interrelated biological processes, highly expressed in porcine pituitary. Norepinephrine (NE), acting as an important neurotransmitter or/and a hormone secreted excessively under stress, affects the synthesis and secretion of various hormones, including pituitary follicle-stimulating hormone (FSH) and luteinizing hormone (LH), which are the key hormones which regulate sexual maturation and reproductive functions. However, the relationship among NE, miR-7 and gonadotropin needs to be elucidated. The aim of this study was to identify whether miR-7 involved in the NE-adrenoceptor signaling pathway affects the synthesis and secretion of FSH and LH in porcine pituitary. Our results showed that the NE intracerebroventricular injection increased pituitary miR-7 level and the synthesis and secretion of FSH and LH in porcine, whereas the inhibition of either endogenous miR-7 or β-adrenergic receptors hindered the rise of FSH and LH synthesis induced by NE in cultured primary porcine anterior pituitary cells. Further, we identified the molecular type of β-adrenergic receptors and the signaling pathway in porcine pituitary, and we found that NE played its roles relying on adrenoceptor beta 2 (β2AR) and the RAF/MEK/ERK1/2 signaling pathway. The phosphorylation of ERK1/2 upregulated miR-7 level which subsequently enhanced FSH and LH synthesis by targeting to Golgi glycoprotein 1 ( GLG1 ). These suggest that miR-7 mediates NE's effect on promoting FSH and LH synthesis in porcine pituitary.